Počiatky fotografie na Slovensku: 1839-1918 : = Beginnings of photography in Slovakia: 1839-1918 - Kleibl, Martin (2020)
The book Beginnings of photography in Slovakia does not aim to present complete and definitive interpretation of the development of the history of photography in this era – because the subjects still hides numerous unexplored territories. This publication should serve as a stepping stone that provides all basic information on the historical context of the origin and development of photography in the world and in Slovakia. It acquaints readers with the historical photographic processes and techniques and introduces various significant figures that fundamentally influenced the development of photography in our region. The book should thus become a basic source of information for a broad audience, as it – through captivating form and a rich picture section – aims to awake interest in the not very well known and unpopular period of the history of photography